2004
DOI: 10.1111/j.1748-5827.2004.tb00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Infections of the subcutis and skin of dogs caused by rapidly growing mycobacteria

Abstract: Nine dogs with panniculitis due to rapidly growing mycobacteria (RGM) were examined over 17 years. Dogs were two to 15 years; five were male, four were female. All were obese or in good condition. Antecedent injury, typically a dog bite or vehicular trauma, could be identified in some patients, while one bitch had hyperadrenocorticism. Infections involved different locations, although the cervicothoracic region, dorsum or flank were most often affected. Patients were systemically well, apart from one dog with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 34 publications
(35 reference statements)
3
62
0
Order By: Relevance
“…Some dogs have a history of bite wounds or trauma. 73 Concurrent hyperadrenocorticism was described in one dog. 75 M. fortuitum can cause pulmonary disease in dogs 76-79 as well as bacteremia.…”
Section: Etiology and Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation
“…Some dogs have a history of bite wounds or trauma. 73 Concurrent hyperadrenocorticism was described in one dog. 75 M. fortuitum can cause pulmonary disease in dogs 76-79 as well as bacteremia.…”
Section: Etiology and Epidemiologymentioning
confidence: 98%
“…[72][73][74][75] No age, breed, or sex predisposition has been recognized, but most dogs are in good body condition or obese. Some dogs have a history of bite wounds or trauma.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…11,45,48,54,55 S. schenckii survives in the environment, typically in decaying vegetation, and people and animals Zoonotic transmission of S. schenckii between cats and people has been documented and is considered an emerging zoonosis.…”
Section: Sporotrichosismentioning
confidence: 99%
“…In addition to FPV, the newer canine variants of canine parvovirus (CPV), specifically CPV-2a, CPV-2b, and CPV-2c reacquired the ability to replicate and cause disease in cats. 55,124,134 One of these variants contains a mutation at amino acid residue 426 of the major capsid protein, an important antigenic epitope of CPV, leading to substitution of an aspartic acid residue with glutamic acid. Parvoviruses are small nonenveloped viruses with a single-stranded DNA genome.…”
Section: Feline Panleukopeniamentioning
confidence: 99%
“…in histological specimens, even with acid-fast stains and especially the NTM. Some factors in tissue fixation may affect the ability of the organism to take up and retain the stain (Malik et al, 2004). In previous studies of NTM infection, acid-fast bacilli were observed in only 5 of 24 human patients, while a diagnosis was made in 20 of these 24 patients using PCR analysis on extracts from formalin-fixed and paraffin wax-embedded tissues (Hsiao et al, 2010).…”
mentioning
confidence: 99%